Jurnal Perbandingan Analisis Metode Saw Dan Topsis (Studi Kasus Percetakan) - Setiawan, Pamuji (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
In the analysis of decision making on problems based on subjective personal analysis without using a particular method, there is usually a high error rate so this will endanger decision making which will lead to regret. There are several types of methods and one of them is the Decision Support System (DSS) method which can be used for the decision making process, but there are 2 methods that are often used in analyzing the decision making process, namely the Simple Additive Weighting (SAW) method and Technique For Others Referencean by Similarity to Ideal Solution (TOPSIS). To find out the best name between the two methods, several weighting changes were made and the test results showed similarities in the decision making (problem solving) process. The purpose of this research is whether decision making can use one of the SAW or TOPSIS methods. From this, it can result in a ranking of the 2 methods that produce the best solutions, which will determine strategic locations to increase the turnover of printing businesses (MSMEs).